2019
DOI: 10.1111/jgs.16205
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Infections in Older Adults: Vaccination

Abstract: All living beings are at risk for experiencing infections; humans are no exception. The prestige and credibility of modern medicine is built in large part on achievements in preventing and treating infectious diseases. For most of human history, there was little that could be done to prevent and treat infections. Millions of humans, of all ages, have died from infections; and in some parts of the world, infection‐related deaths remain common. Advances in preventing and treating infectious diseases include impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Infections. Nowadays, vaccination has gained increasing attention owing to its promising results to combat various infections and to reduce the costs as well as deaths worldwide [128]. The recent rapid emergence of CoV infection has shown that vaccination can act as a significant function in managing the social safety and public health.…”
Section: Nanotechnology-based Vaccines For Coronavirusmentioning
confidence: 99%
“…Infections. Nowadays, vaccination has gained increasing attention owing to its promising results to combat various infections and to reduce the costs as well as deaths worldwide [128]. The recent rapid emergence of CoV infection has shown that vaccination can act as a significant function in managing the social safety and public health.…”
Section: Nanotechnology-based Vaccines For Coronavirusmentioning
confidence: 99%
“…6 Therefore, multiple variables need to be considered when deciding which vaccinations to administer to older adults. 7 The increased susceptibility to infections and reduced immune response to vaccination are due to altered aging-related reactions identified in almost all immune cells. These changes also result in increased inflammatory markers in a variety of tissues in the body.…”
Section: Older Adultsmentioning
confidence: 99%
“…-severe infection 7 -pneumonia 7 -hospitalization 7 -risk of death 7 -strokes, congestive heart failure, ischemic heart disease, cancer, and hip fracture, have all been linked to influenza 32 Increased risk of pneumococcal infection 6 Pneumococcal-related complications: -hospitalization 6 -death 7 -higher incidence of CAP, IPD, and related mortality 7 Herpes zoster: -increased risk of varicella virus reactivation (i.e., herpes zoster or shingles) and greater disease severity 11,33 -PHN, whit severe neuropathic pain for months or years 7 -excess risk of stroke amounting to 30% in the year after HZ onset 34 Tetanus: -higher incidence and higher mortality rate if infected 7 Pertussis: -severe symptoms and increased mortality 11,35 Influenza vaccination: -reduced risk of ischemic stroke and acute myocardial infarction by a third 3,36 Influenza and PPV vaccination:-reduced risk of death and of coronary and intensive care admissions in the year following vaccination 3,36 Zoster vaccine:…”
Section: Influenza-related Complicationsmentioning
confidence: 99%
“…As a result of these outbreaks there is an urgent need to focus on the development and evaluation of interventions to increase vaccine uptake to protect the expanding demographic of the older adult (aged ≥ 65 years) population (Privor-Dumm et al, 2020;Williams et al, 2020). Due to decreased immunity and greater likelihood of existing chronic health conditions, older adults are more susceptible to infectious diseases and have altered immune response to vaccinations (Coll et al, 2020;Russell et al, 2018). Vaccination can support healthy ageing and efforts to increase uptake among older adults seek to reduce morbidity, mortality, and loss of quality of life associated with VPDs (Ozawa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%